Influence of maxillary canine torque variations on the perception of smile esthetics among orthodontists and laypersons - Thiago Correia Barbosa Lemos; Juliana de Brito Vasconcelos; Bianca Mota dos Santos; Andre Wilson Machado
ABSTRACT Objective: The purpose of this study was to determine the perception of smile esthetics among orthodontists and laypersons with respect to unilateral maxillary canine torque variations in a frontal smile analysis. Methods: Full face and close-up smile photographs of two subjects (1 man and 1 woman) were used. Both smiles displayed healthy maxillary anterior dentitions. The images were digitally altered to obtain a bilateral 0° torque in the maxillary canines. From this image, unilateral variations of the left canine were made with -15°, -10°, -5°, 0°, +5°, +10° and +15°. Final images were randomly assembled into an album that was given to 53 orthodontists and 53 laypersons. Each rater was asked to evaluate the attractiveness of the images using visual analog scales. Data collected were statistically analyzed with one-way analysis of variance with Tukey post-hoc test and the unpaired Student t test. Results: For orthodontists, most attractive smiles were those with 0°, -5° and -10°. For laypersons, most attractive smiles were those with 0°, -5°, -10°, -15° and + 5°. For both groups, the lowest scores were given for the smiles with +10° and +15° torque. When comparing the perceptions of the orthodontists and laypersons, they did not show statistical differences in most situations. Moreover, in general, there was no significant difference between the full-face and close-up assessments of the smiles. Conclusions: The present findings indicated that smiles with unilateral palatal (negative values) maxillary canine torque variations were more tolerated than smiles with buccal crown torque (positive values) variations.